The prevalence of idiopathic hirsutism and polycystic ovary syndrome in the Tehran Lipid and Glucose Study - Azizi Fereidoun; Rashidi Homeira; Tehrani Fahimeh (BMC, 2011)
Abstract Background There is no clear and contemporaneous method for screening of idiopathic hirsutism (IH) and polycystic ovary syndrome (PCOS) at the community level and current estimates regarding their prevalence are limited. We aimed to ascertain the prevalence of IH and PCOS in a randomly selected sample of reproductive aged female participants of the Tehran Lipid and Glucose Study (TLGS). Methods One thousand and two women, aged 18-45 years, were randomly selected from among reproductive aged women who participated in the TLGS. Those women with either hirsutism or menstrual dysfunction were assessed for biochemical hyperandrogenemia; whereas those participants with hirsutism per se were further assessed for subclinical menstrual dysfunction. PCOS were diagnosed using the National Institute of Health (NIH) criteria. IH was defined as hirsutism without clinical or sub clinical menstrual dysfunction or biochemical hyperandrogenemia (BH). Results The mean ± SD of age of study population was 29.2 ± 8.7 years. Estimated prevalences of idiopathic hirsutism and pure menstrual dysfunction were 13.0% (95% CI: 10.9%-15.1%) and 1.5%(95% CI: 1.1%-1.9%), respectively. The prevalence of PCOS was 8.5% (95% CI: 6.8% - 10.2%); more than one third of these cases would possibly have remained undiagnosed or misdiagnosed, had we not assessed them for subclinical menstrual dysfunction or biochemical hyperandrogenemia. Conclusions These data from a large representative and non selected population of women confirm the concept that IH and PCOS are the two most common gynecological endocrinopathies among reproductive aged women. The estimated prevalence of these conditions is highly influenced by their screening methods at the community level.